Efficacy of migraine prophylaxis treatments for treatment-naïve patients and those with prior treatment failure: a protocol for systematic review and network meta-analysis of randomised controlled trials - Gareth Mckay; Ammarin Thakkinstian; John Attia; Thunyarat Anothaisintawee; Pawin Numthavaj (BMJ Open)
Introduction Migraine headache is a significant health problem affecting patients’ psychological well-being and quality of life. Several network meta-analyses (NMAs) have compared the efficacy of migraine prophylaxis medications. However, some have focused exclusively on oral medications, while others were limited to injectable medications. Moreover, none of these NMAs conducted a stratified analysis between treatment-naïve patients and those with prior treatment failure. Therefore, this systematic review and NMA will compare the efficacy among all treatments for migraine prophylaxis, stratified by the treatment status of patients (ie, treatment-naïve and previous treatment failure).Methods and analysis Randomised-controlled trials that included patients with chronic or episodic migraine, assessed the efficacy of oral or injectable treatments for migraine prophylaxis and measured the outcomes as monthly migraine day, monthly headache day, migraine-related disability, health-related quality of life or adverse drug events will be eligible for inclusion in this review. Relevant studies will be searched from Medline, Scopus, the US National Institutes of Health Register, and the World Health Organization International Clinical Trials Registry Platform (WHO-ICTRP) databases since inception through 15 August 2023. Risk of bias assessment will be performed using a revised tool for assessing the risk of bias in randomised trials. Two-stage NMA will be applied to compare relative treatment effects among all treatments of migraine prophylaxis. Surface under the cumulative ranking curve will be applied to estimate and rank the probability to be the best treatment. Consistency assumption will be assessed using a design-by-treatment interaction model. Publication bias will be assessed by comparison-adjusted funnel plot. All analyses will be stratified according to patients’ status (ie, treatment-naïve and prior treatment failure).Ethics and dissemination This study is a systematic review protocol collecting data from published literature and does not require approval from an institutional review board. Results from this systematic review will be published in a peer-reviewed journal.PROSPERO registration number CRD42020171843.